2020
DOI: 10.3390/en13123037
|View full text |Cite
|
Sign up to set email alerts
|

Underwater Noise Emission Due to Offshore Pile Installation: A Review

Abstract: The growing demand for renewable energy supply stimulates a drastic increase in the deployment rate of offshore wind energy. Offshore wind power generators are usually supported by large foundation piles that are driven into the seabed with hydraulic impact hammers or vibratory devices. The pile installation process, which is key to the construction of every new wind farm, is hindered by a serious by-product: the underwater noise pollution. This paper presents a comprehensive review of the state-of-the-art com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 162 publications
(279 reference statements)
0
14
1
1
Order By: Relevance
“…Several studies reported that the noise level of pile driving noise near the seafloor was generally higher than at the sea surface (Reinhall and Dahl, 2011;Tsouvalas, 2020). However, in our case, which was measured at approximately 640 m from the pile in 2017, the sound exposure level and the peak pressure level were the lowest at 5 m above the seafloor, and rather higher at 3 and 7 m above the seafloor, as shown in Figures 5A,B.…”
Section: Summary and Discussioncontrasting
confidence: 55%
See 3 more Smart Citations
“…Several studies reported that the noise level of pile driving noise near the seafloor was generally higher than at the sea surface (Reinhall and Dahl, 2011;Tsouvalas, 2020). However, in our case, which was measured at approximately 640 m from the pile in 2017, the sound exposure level and the peak pressure level were the lowest at 5 m above the seafloor, and rather higher at 3 and 7 m above the seafloor, as shown in Figures 5A,B.…”
Section: Summary and Discussioncontrasting
confidence: 55%
“…As onshore wind farms are often accompanied by landscape damage and noise, offshore wind power generation has been considered an attractive alternative. There are several foundation types of offshore wind turbine construction such as monopiles, tripods, steel jackets, suction caisson, gravity-based structure and floating (Sánchez et al, 2019;Tsouvalas, 2020). Among them, processes involving percussive pile driving produce underwater noise with extremely high sound pressure levels.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The increase of installed capacity came along with a general growth in wind turbine size, distance to shore and water depth of the installed and planned wind farms in the last decade. Consequently, researchers and industries had to face and are still facing many challenges regarding design, production, installation, operability, maintenance and decommissioning of these new and bigger offshore wind turbines [3,4].…”
Section: Introductionmentioning
confidence: 99%